Penapisan PGPF untuk Pengendalian Penyakit Busuk Lunak Lidah Buaya (Aloe vera) di Tanah Gambut - Supriyanto Supriyanto; Achmadi Priyatmojo; Triwidodo Arwiyanto (Jurnal Perlindungan Tanaman Indonesia, 2009)
Aloe (Aloe vera) planted in West Borneo peat soil is well known as having the best product quality in Indonesia. Soft rot disease is one of the constraints of Aloe cultivation on peat soil. Many methods have no significant result for controlling this disease. This research objectives are to obtain Plant Growth Promoting Fungi (PGPF) for controlling Aloe bacterial soft rot in peat soil. The research was conducted in Clinical Laboratory of Plant Pathology and glass house of Faculty of Agriculture, Gadjah Mada University, Yogyakarta from October 2008 to September 2009. The methods included fungal isolation from peat land, hypovirulent and PGPF ability test, and biological control test in the glass house. Among 42 peat soil fungi tested, 28 isolates were hypovirulent and only 2 isolates i.e. SNTH001 (Penicillium sp.) and SNTH003 (Aspergillus sp.) showed the PGPF ability. Glass house trial showed that single application of SNTH001 and SNTH003 isolates were able to increase the growth of Aloe. In the biological control of Aloe soft rot disease test showed that the lowest intensity (25%) might be obtained by using SNTH001 isolate.